PENGARUH CORPORATE GOVERNANCE, LIKUIDITAS, PROFITABILITAS, DAN ENTERPRISE SIZE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (Studi Empiris pada Perusahaan Sektor Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020) - Prabawati Sholihah; Wahyono Wahyono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Along with the development of the economic sector in Indonesia, especially in the consumer goods industry sector, which is an industry whose business is engaged in producing the basic needs of the Indonesian people, there has certainly been a lot of progress. Progress in consumer goods companies can be seen in the number of consumer goods companies that have been listed on the Indonesia Stock Exchange and also many companies that have gone public. This study aims to determine how the influence of managerial ownership, profitability, liquidity and enterprise size on corporate social responsibility disclosure by using a quantitative and purposive approach for sampling methods. The results of this study indicate that liquidity and profitability have an effect on corporate social responsibility disclosure, meanwhile managerial ownership and business size have no effect on corporate social responsibility disclosure.